Adolescent Identity Struggles, Vocational Guidance and Career Counselling: A Case Study - Janetius, S.T.; Ahammed, A.V. Hashir (International Journal of Indian Psychology, 2017)
Adolescence is a critical stage of human development that needs special attention and direction. Psychologists identify this period as quarter-life transition due to the silent struggle and crisis many adolescents face in this crucial period. Identity creation is the major psychosocial task identified by Erikson and Marcia who made elaborate studies on adolescents. If proper guidance is not provided, adolescents struggle and wobble in their steady growth and identity creation. Influenced by peers, adolescents are confused and confronted by realities which are beyond their aptitude and interests. As career choice takes precedence in identity creation, identifying the aptitude and interests and, relating this to their vocational preference plays a major role. This case study elaborates the identity struggle and the role of vocational guidance and counselling intervention in helping an adolescent in his growth and development.